2018
DOI: 10.1002/app.46512
|View full text |Cite
|
Sign up to set email alerts
|

Reliable surface modification of dental plastic substrates to reduce biofouling with a photoreactive phospholipid polymer

Abstract: Plastic substrates have been widely applied in clinical settings for dental treatments. These substrates should be strong enough for long‐term implantation in the oral cavity and should be resistant to biofouling. We developed a new photoreactive phospholipid polymer to reduce biofouling on dental plastics via a photochemical reaction. Poly(methyl methacrylate) (PMMA) and poly(ether ether ketone) (PEEK) were used as dental plastics. To determine the antibiofouling properties on the polymer surface, the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Ionic phosphodiester‐based materials tend to show excellent cellular compatibility, hemocompatibility and a resistance to adsorption of proteins . Adsorption of proteins can induce an inflammatory foreign‐body response so this adverse response will be much reduced in the case of phosphodiester‐coated surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Ionic phosphodiester‐based materials tend to show excellent cellular compatibility, hemocompatibility and a resistance to adsorption of proteins . Adsorption of proteins can induce an inflammatory foreign‐body response so this adverse response will be much reduced in the case of phosphodiester‐coated surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Control of composition is difficult. Since PEEK absorbs ultraviolet irradiation, it was used for chemical surface modification and grafting [18][19][20]. Due to the high-energy treatments, a high diversity of different functional groups are formed on the surface, but the effect is usually not permanent [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Two main strategies have been used to prevent implant-related infection: (1) minimizing the bacterial attachment or (2) killing bacteria present on the surface of the implant. In the first category, Ishihari et al grafted a coating of poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC), a highly hydrophilic polymer, onto the surface of PEEK via photo-induced graft polymerization of MPC [11] or via aryl-azide UV photoinsertion of PMPC [12]. It was found that the increased surface wettability of PEEK-PMPC (< 10° for PEEK-PMPC compared to 90° for untreated PEEK) offered a certain degree of protection in vitro against E. coli adhesion [13].…”
Section: Introductionmentioning
confidence: 99%